Neuronopathic Gaucher disease: Beyond lysosomal dysfunction - Arévalo, Nohela B.; Lamaizon, Cristian M.; Cavieres, Viviana A.; Burgos, Patricia V.; Álvarez, Alejandra R.; Yañez, María J.; Zanlungo, Silvana (Frontiers in Molecular Neuroscience, 2022)
Gaucher disease (GD) is an inherited disorder caused by recessive mutations in the GBA1 gene that encodes the lysosomal enzyme β-glucocerebrosidase (β-GC). β-GC hydrolyzes glucosylceramide (GluCer) into glucose and ceramide in the lysosome, and the loss of its activity leads to GluCer accumulation in different tissues. In severe cases, enzymatic deficiency triggers inflammation, organomegaly, bone disease, and neurodegeneration. Neuronopathic Gaucher disease (nGD) encompasses two different forms of the disease, characterized by chronic or acute damage to the central nervous system (CNS). The cellular and molecular studies that uncover the pathological mechanisms of nGD mainly focus on lysosomal dysfunction since the lysosome is the key organelle affected in GD. However, new studies show alterations in other organelles that contribute to nGD pathology. For instance, abnormal accumulation of GluCer in lysosomes due to the loss of β-GC activity leads to excessive calcium release from the endoplasmic reticulum (ER), activating the ER-associated degradation pathway and the unfolded protein response. Recent evidence indicates mitophagy is altered in nGD, resulting in the accumulation of dysfunctional mitochondria, a critical factor in disease progression. Additionally, nGD patients present alterations in mitochondrial morphology, membrane potential, ATP production, and increased reactive oxygen species (ROS) levels. Little is known about potential dysfunction in other organelles of the secretory pathway, such as the Golgi apparatus and exosomes. This review focuses on collecting evidence regarding organelle dysfunction beyond lysosomes in nGD. We briefly describe cellular and animal models and signaling pathways relevant to uncovering the pathological mechanisms and new therapeutic targets in GD.